2022
DOI: 10.3390/cells11243989
|View full text |Cite
|
Sign up to set email alerts
|

cfDNA Methylation Profiles and T-Cell Differentiation in Women with Endometrial Polyps

Abstract: DNA methylation is a part of the regulatory mechanisms of gene expression, including chromatin remodeling and the activity of microRNAs, which are involved in the regulation of T-cell differentiation and function. However, the role of cfDNA methylation in T-cell differentiation is entirely unknown. In patients with endometrial polyps (EPs), we have found an imbalance of T-cell differentiation and an aberrant cfDNA methylation profile, respectively. In this study, we investigated the relationship between cfDNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…A prior study showed that progesterone could regulate EPs by modulating the expressions of long non-coding RNA H19 and microRNA-152 to influence Wnt and β-catenin signaling [ 2 ]. Furthermore, the correlation between cell-free DNA methylation profiles and T-cell differentiation in endometrial polyp patients can help explain the pathogenesis of polyps [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…A prior study showed that progesterone could regulate EPs by modulating the expressions of long non-coding RNA H19 and microRNA-152 to influence Wnt and β-catenin signaling [ 2 ]. Furthermore, the correlation between cell-free DNA methylation profiles and T-cell differentiation in endometrial polyp patients can help explain the pathogenesis of polyps [ 40 ].…”
Section: Discussionmentioning
confidence: 99%